Desain Showroom dan Booth Centimeter Home and Furniture Furnishing dengan Konsep House In a House - Wahyudi, Kathleen Stenecia; Purwoko, Gervasius Herry; Prihatmanti, Rani (Universitas Ciputra Surabaya, 2015)
The demand of comfortability in a house has become an important factor. Because of that, any aspect that relates with it has to be well-designed. So, the people that live it in that house feel maycomfortable and that feeling has to be illustrated in the design. The priority for designing the showroom and booth is the comfort matter. Because of that, the idea for the design concept of this project is ‘House in a House’. In another words, it could be defined that the house ambience is illustrated in the showroom as well as in the exhibition booth. Inside the showroom, objects sold are the home furnishing products, including the furniture furnishing products. The most important thing of the design concept is a simple design. Therefore, it will give a relieved and roomy ambience, with black and white colour, and with the consideration of ergonomic, circulation arrangement, and room organizization. The showroom and the exhibition booth that were designed, were attractive and might invite people to buy the products, and the customer understand about the products sold.